1992
DOI: 10.1111/j.1432-1033.1992.tb17503.x
|View full text |Cite
|
Sign up to set email alerts
|

Overproduction of prismane protein in Desulfovibrio vulgaris (Hildenborough): evidence for a second S= 1/2‐spin system in the one‐electron reduced state

Abstract: The gene encoding the prismane protein from Desulfovibrio vulgaris (Hildenborough) was inserted into broad-host-range vector pSUP104. The recombinant plasmid, pJSP104, was transferred to D. vulgaris by conjugal plasmid transfer. In the transconjugant D. vulgaris cells the prismane protein was 25-fold overproduced. The overproduced prismane protein was characterized by molecular mass, isoelectric point, iron content and spectroscopical properties. Both the iron content and the ultraviolet/ visible spectrum are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
12
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
3
2
2

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 43 publications
(13 reference statements)
2
12
0
Order By: Relevance
“…Midpoint potentials calculated for the redox transitions of the hybrid cluster 2 are −50, +85 and +385 mV. The overall pattern for the three redox transitions of the hybrid cluster is similar to that found for Desulfovibrio HCPs [4,5,8]; midpoint potentials for the ‘+3/+4’ and ‘+4/+5’ transitions in E. coli HCP are, however, ≈ 100 mV more positive than in HCPs from Desulfovibrio species.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations
“…Midpoint potentials calculated for the redox transitions of the hybrid cluster 2 are −50, +85 and +385 mV. The overall pattern for the three redox transitions of the hybrid cluster is similar to that found for Desulfovibrio HCPs [4,5,8]; midpoint potentials for the ‘+3/+4’ and ‘+4/+5’ transitions in E. coli HCP are, however, ≈ 100 mV more positive than in HCPs from Desulfovibrio species.…”
Section: Resultssupporting
confidence: 70%
“…HCP and the gene encoding this protein have previously been isolated from D. vulgaris (Hildenborough) and D. desulfuricans ATCC 27774 [1–4,8,21,22]. Cross‐reactivity with antibodies and hybridization with nucleic acid probes indicated that proteins and DNA sequences with similarity to D. vulgaris HCP and the hcp gene, respectively, also occur in other strictly anaerobic sulfate‐reducing bacteria [2,22].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Its up-regulation in the presence of nitrite and nitrate suggests that HCP is involved in nitrite or nitrate reduction. Being a redox-active protein, based on the structural and spectroscopic studies [3,10,11], HCP appears to accomplish an as yet unidentified reaction in the nitrogen cycle. To investigate this possibility HCP has been overexpressed from a recombinant plasmid for physiological studies.…”
Section: Discussionmentioning
confidence: 99%